2D versus 3D visualization: impact on laparoscopic proficiency using the fundamentals of laparoscopic surgery skill set - Tanagho, Youssef S; Andriole, Gerald L; Paradis, Alethea G; Madison, Kerry M; Sandhu, Gurdarshan S; Varela, J Esteban; Benway, Brian M (Journal of laparoendoscopic & advanced surgical techniques. Part A, 2012)
We compared the impact of two-dimensional (2D) versus three-dimensional (3D) visualization on both objective and subjective measures of laparoscopic performance using the validated Fundamentals of Laparoscopic Surgery (FLS) skill set. Thirty-three individuals with varying laparoscopic experience completed three essential drills from the FLS skill set (peg transfer, pattern cutting, and suturing/knot tying) in both 2D and 3D. Participants were randomized to begin all tasks in either 2D or 3D. Time to completion and number of attempts required to achieve proficiency were measured for each task. Errors were also noted. Participants completed questionnaires evaluating their experiences with both visual modalities. Across all tasks, greater speed was achieved in 3D versus 2D: peg transfer, 183.4 versus 245.6 seconds (P<.0001); pattern cutting, 167.7 versus 209.3 seconds (P=.004); and suturing/knot tying, 255.2 versus 329.5 seconds (P=.031). Fewer errors were committed in the peg transfer task in 3D versus 2D (P=.008). Fourteen participants required multiple attempts to achieve proficiency in one or more tasks in 2D, compared with 7 in 3D. Subjective measures of efficiency and accuracy also favored 3D visualization. The advantage of 3D vision persisted independent of participants' level of technical expertise (novice versus intermediate/expert). There were no differences in reported side effects between the two visual modalities. Overall, 87.9% of participants preferred 3D visualization. Three-dimensional vision appears to greatly enhance laparoscopic proficiency based on objective and subjective measures. In our experience, 3D visualization produced no more eye strain, headaches, or other side effects than 2D visualization. Participants overwhelmingly preferred 3D visualization.